Analysis of transmission of novel polymorphisms in the somatostatin receptor 5 (SSTR5) gene in patients with autism - Lauritsen, Marlene (Am J Med Genet B Neuropsychiatr Genet, 2003)
Infantile autism is a pervasive developmental disorder with a strong genetic component. The mode of inheritance appears to be complex and no specific susceptibility genes have yet been identified. Chromosome 16p13.3 may contain a susceptibility gene based on findings from genome scans and reports of chromosome abnormalities in individuals with autism. The somatostatin receptor 5 (SSTR5) gene is located on chromosome 16p13.3 and is thus a positional candidate gene for autism. SSTR5 may also be a functional candidate gene for autism because somatostatin inhibits growth hormone secretion, and increased growth hormone response has been reported in some individuals with autism. Moreover, the somatostatinergic system interacts with the dopaminergic system, which has been hypothesized to be involved in the etiology of autism; in particular, somatostatin secretion is regulated by dopamine, and the dopamine D2 receptor and the SSTR5 receptor interact to form a receptor complex with enhanced functional activity. In the present study we tested whether the alleles of twelve new single nucleotide polymorphisms (SNPs) in the SSTR5 gene were preferentially transmitted using the transmission disequilibrium test (TDT) in a sample of 79 trios with autism (18 from Denmark and 61 from France). Furthermore, we combined four missense SNPs into haplotypes and searched for preferential transmission using the program TRANSMIT. No significant preferential transmission of the alleles and haplotypes of the twelve SNPs was found. Our results do not suggest the SSTR5 gene as a susceptibility gene for autism.